Epoxy resin, curable resin composition, cured product, fiber-reinforced composite material, and fiber-reinforced resin molded product

JP7632036B2Active Publication Date: 2025-02-19DIC CORP
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
JP2021076421
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-28
Publication Date
2025-02-19
Estimated Expiration
2041-04-28

Smart Images

  • Figure 0007632036000009
    Figure 0007632036000009
  • Figure 0007632036000010
    Figure 0007632036000010
  • Figure 0007632036000011
    Figure 0007632036000011
Patent Text Reader

Abstract

To provide an epoxy resin which is formed from a phenol resin having such a specific structure as to obtain a cured product having high heat resistance and high flexural characteristics (flexural strength and flexural modulus), a curable resin composition containing the epoxy resin, a cured product obtained from the curable resin composition, a fiber-reinforced composite material, and a fiber-reinforced resin molding.SOLUTION: A phenol resin is a reactant of a phenol resin which is a reactant of a catechol compound and aliphatic ketone, and has at least two catechol skeletons derived from the catechol compound, and an epoxy resin is a reactant having a glycidyl ether group obtained by reacting a phenolic hydroxyl group of the phenol resin and epihalohydrin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin obtained from a phenolic resin having a specific structure, a curable resin composition containing the epoxy resin, a cured product obtained from the curable resin composition, a fiber-reinforced composite material, and a fiber-reinforced resin molded product. [Background technology]

[0002] Curable resin compositions containing an epoxy resin and a curing agent therefor as essential components have excellent mechanical strength, heat resistance, water resistance, chemical resistance, insulating properties, and the like in the cured product, and therefore are widely used in a wide range of applications, such as matrices for fiber-reinforced composite materials, heat dissipation components, paints, semiconductors, and printed wiring boards.

[0003] In particular, fiber-reinforced plastic molded products made with reinforcing fibers have attracted attention for their lightweight yet excellent mechanical strength characteristics, and their use is expanding in a variety of structural applications, including housings and various components for automobiles, aircraft, ships, etc. In particular, as carbon fiber composite materials (CFRP) are increasingly being used in the aircraft and automotive fields, the amount of epoxy resin used as their matrix resin is steadily increasing.

[0004] Currently, epoxy resins that are mainly used in applications for carbon fiber composite materials include diglycidyl ether of bisphenol A and tetraglycidylamine of diaminodiphenylmethane (TGDDM) (see, for example, Patent Document 1). These epoxy resins meet a certain level of the required properties for applications of carbon fiber composite materials, such as elastic modulus, strength, heat resistance, and moist heat resistance.

[0005] However, there is currently a market need for even higher heat resistance and higher elastic modulus, and the physical properties of the above epoxy resins do not yet fully satisfy the market demand. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2003-201388 A Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, an object of the present invention is to provide an epoxy resin capable of giving a cured product having high heat resistance and high bending properties (such as bending strength and bending modulus), a curable resin composition containing the epoxy resin, a cured product obtained from the curable resin composition, a fiber-reinforced composite material, and a fiber-reinforced resin molded product. [Means for solving the problem]

[0008] Therefore, the present inventors conducted extensive research to solve the above problems, and as a result, discovered that a cured product obtained by using a curable resin composition containing an epoxy resin obtained from a phenolic resin having a specific structure exhibits high heat resistance and high bending properties (such as bending strength and bending modulus), thereby completing the present invention.

[0009] That is, the present invention relates to a reaction product of a catechol compound and an aliphatic ketone, the reaction product being a phenolic resin having at least two catechol skeletons derived from the catechol compound; The present invention relates to an epoxy resin which is a reaction product having a glycidyl ether group obtained by reacting a phenolic hydroxyl group of the phenol resin with an epihalohydrin.

[0010] The present invention relates to a curable resin composition comprising the above-mentioned epoxy resin.

[0011] The present invention relates to a cured product obtained by subjecting the curable resin composition to a curing reaction.

[0012] The present invention relates to a fiber-reinforced composite material comprising the above-mentioned curable resin composition and reinforcing fibers.

[0013] The present invention relates to a fiber-reinforced resin molded product comprising the above-mentioned cured product and reinforcing fibers. Effect of the Invention

[0014] According to the present invention, a cured product obtained by using the obtained epoxy resin is useful because it can exhibit high heat resistance and high bending properties (such as bending strength and bending modulus). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] [Phenol resin] The present invention relates to an epoxy resin which is a reaction product of a catechol compound and an aliphatic ketone, the epoxy resin being characterized in that it is a reaction product having a phenolic resin having at least two catechol skeletons derived from the catechol compound, and a glycidyl ether group obtained by a reaction between a phenolic hydroxyl group of the phenolic resin and an epihalohydrin. The phenolic resin is preferably polyfunctional because it contains at least two catechol skeletons (having two hydroxyl groups as substituents on an aromatic ring, and the two hydroxyl groups are in an ortho-position relationship with each other) derived from the catechol compound. The phenolic resin preferably contains at least two catechol skeletons, and may contain three or more catechol skeletons, but the phenolic resin is particularly preferably used in the case of two catechol skeletons, because the phenolic resin has a low melt viscosity.

[0016] In the present invention, the "phenolic resin" refers to a resin containing a phenolic hydroxyl group, and the "epoxy resin" refers to a resin containing a glycidyl ether group. The "catechol skeleton" refers to a skeleton "having two hydroxyl groups as substituents on an aromatic ring, the two hydroxyl groups being in an ortho-position relationship with respect to each other," or a skeleton from which the hydrogen atoms constituting the hydroxyl groups have been removed.

[0017] [Catechol compounds] The phenolic resin is a reaction product of a catechol compound and an aliphatic ketone. The catechol compound is a dihydroxybenzene having hydroxyl groups at the 1st and 2nd positions, and may have a substituent on the aromatic ring of the catechol compound, but it is particularly preferable from the viewpoint of bending properties that the catechol compound has no substituent (catechol). By using the catechol compound, the phenolic resin includes a catechol skeleton, and it is presumed that the intermolecular density is increased due to the π-π interaction between molecules based on the aromatic ring, and a cured product having excellent mechanical strength and heat resistance can be obtained, which is preferable.

[0018] The substituent may be a hydrocarbon group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a halogen atom, and may be an alkyl group such as a methyl group, and the position and number of the substituent are not particularly limited. If the number of carbon atoms in the hydrocarbon group or the like exceeds 4, steric hindrance becomes too large, and reactivity becomes too low during synthesis of the phenolic resin or during synthesis of the epoxy resin described below, and the mechanical strength of the obtained cured product decreases, which is not preferable.

[0019] The catechol compound may be used alone, or a plurality of compounds having different positions of substituents may be used in combination.

[0020] [Aliphatic ketones] The phenolic resin is characterized by being a reaction product of a catechol compound and an aliphatic ketone. By introducing a skeleton (e.g., -C(-R)(-R')-) based on the reaction between the catechol compound and the aliphatic ketone (e.g., represented by RC(=O)-R', where R and R' are hydrocarbon groups) into the phenolic resin, the intermolecular interaction is appropriately weakened, resulting in a phenolic resin with low melt viscosity and excellent handling properties, which is preferable. In addition, the resulting cured product is useful because it has an excellent balance between heat resistance and mechanical strength.

[0021] Examples of the aliphatic ketone include acetone, methyl ethyl ketone, diethyl ketone, methyl propyl ketone, methyl isobutyl ketone, methyl amyl ketone (2-heptanone), cyclopentanone, cyclohexanone, isophorone, cycloheptanone, cyclooctanone, etc. Among them, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc. are preferred from the viewpoint of reactivity during synthesis of the phenolic resin or the epoxy resin, and from the viewpoint of availability.

[0022] The aliphatic ketones may be used alone or in combination of two or more compounds.

[0023] The phenol resin can be obtained by reacting a catechol compound represented by the following general formula (1) with an aliphatic ketone represented by the following general formula (2), to obtain a phenol resin represented by the following general formula (3). [ka] [ka] [ka]

[0024] In the above general formula (1), the substituent R 1 may be a hydrogen atom, a hydrocarbon group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a halogen atom. From the viewpoint of reactivity when used as a raw material and bending properties of a cured product, preferably, the hydrocarbon group having 1 to 4 carbon atoms includes a methyl group, an ethyl group, a propyl group, a butyl group, a t-butyl group, etc., the alkoxy group having 1 to 4 carbon atoms includes a methoxy group, an ethoxy group, a propyloxy group, a butoxy group, etc., and the halogen atom includes a fluorine atom, a chlorine atom, a bromine atom, etc. Among them, the R 1 However, when the substituent is a hydrogen atom, the melt viscosity is low, the handling property is excellent, and the balance between the bending property and the heat resistance is excellent, which is a preferred embodiment.

[0025] In the above general formula (1), m is preferably an integer of 0 to 3, and more preferably an integer of 0 or 1, from the viewpoints of reactivity when used as a raw material and bending properties of the cured product.

[0026] In the above general formula (2), R 2 and R 3 are each independently preferably a hydrocarbon group having 1 to 4 carbon atoms, and from the viewpoint of the heat resistance and bending properties of the cured product, the R 2 and R 3 are each independently a methyl group, an ethyl group, a propyl group, or a butyl group, and more preferably 2 and R 3 Both of these are methyl groups. 2 and R 3 However, since the R is a methyl group or the like, the heat resistance and bending properties of the cured product are well balanced. 2 and R 3 When both R are methyl groups, the melt viscosity is low, the handling property is excellent, and the balance between the bending property and the heat resistance is excellent, which is a preferred embodiment. 2 and R 3 may be bonded to form a cyclic structure (the aliphatic ketone includes an alicyclic ketone).

[0027] In the above general formula (3), n is preferably an integer of 0 to 3. From the viewpoints of ease of adjusting the viscosity of the resulting phenolic resin or epoxy resin to a low value and excellent fluidity and handling properties, n is more preferably an integer of 0 or 1, and even more preferably n is 0 (biscatechol A).

[0028] In addition, R in the above general formula (3) 1 , R 2 , R 3 and m are the same as in the above general formulas (1) and (2).

[0029] The reaction ratio of the catechol compound and the aliphatic ketone is preferably in the range of 0.01 to 0.9 mol, and more preferably 0.1 to 0.7 mol, of the aliphatic ketone per 1 mol of the catechol compound, since this gives an epoxy resin having an excellent balance between the melt viscosity and the heat resistance of the cured product.

[0030] The reaction between the catechol compound and the aliphatic ketone is preferably carried out in the presence of an acid catalyst, since the reaction proceeds efficiently. Examples of the acid catalyst include inorganic acids such as hydrochloric acid, sulfuric acid, and phosphoric acid, organic acids such as methanesulfonic acid, paratoluenesulfonic acid, and oxalic acid, and Lewis acids such as boron trifluoride, anhydrous aluminum chloride, and zinc chloride. In addition, a co-catalyst such as mercaptocarboxylic acids such as thioglycolic acid, thiolactic acid, 2-mercaptopropionic acid, and 3-mercaptopropionic acid, and alkyl mercaptans such as propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, heptyl mercaptan, octyl mercaptan, nonyl mercaptan, decyl mercaptan, undecyl, and dodecyl mercaptan can also be used together with the acid catalyst. The amount of the acid catalyst used is preferably in the range of 0.01 to 5.0% by mass based on the total mass of the reaction raw materials (including the solvent).

[0031] The reaction between the catechol compound and the aliphatic ketone can usually be carried out at a temperature of 30 to 80° C. for 1 to 20 hours. The reaction may be carried out in an organic solvent as needed. The organic solvent used here is not particularly limited as long as it is an organic solvent that can be used under the above temperature conditions, and specific examples include methyl cellosolve, ethyl cellosolve, toluene, xylene, and methyl isobutyl ketone. When using these organic solvents, it is preferable to use them in the range of 10 to 500% by mass based on the total mass of the reaction raw materials.

[0032] After the reaction between the catechol compound and the aliphatic ketone is completed, unreacted reactant materials and by-products are distilled off to obtain a purified phenolic resin. In addition, if a part of the catechol compound remains unreacted after the reaction between the catechol compound and the aliphatic ketone is completed, it may volatilize during the production of a cured product, which may cause voids or cause stoichiometric errors and adversely affect the bending properties of the resulting epoxy resin, so it is preferable that the amount of the catechol compound remaining is not large. Therefore, the content of the remaining (unreacted) catechol compound is preferably 20 area% or less in GPC area%, more preferably 10 area% or less. Here, the GPC area% refers to the value obtained by dividing the GPC peak area value of the remaining (unreacted) catechol compound by the total GPC peak area value of all components.

[0033] The hydroxyl equivalent of the phenolic resin is preferably 50 to 110 g / equivalent, more preferably 60 to 100 g / equivalent, and even more preferably 65 to 90 g / equivalent. When the hydroxyl equivalent is within the above range, the functional group density in the cured product is increased, and the heat resistance and mechanical strength of the obtained cured product are also excellent, which is preferable. The hydroxyl equivalent of the phenolic resin here is based on the measurement method of "hydroxyl equivalent of phenolic resin" in the following examples.

[0034] The melt viscosity (150°C) of the phenolic resin is preferably 5.0 dPa·s or less, more preferably 0.1 to 4.0 dPa·s, and even more preferably 0.5 to 3.0 dPa·s. When the melt viscosity of the phenolic resin is within the above range, the resin has low viscosity and excellent fluidity and handleability, and is therefore preferable in terms of handleability during epoxy resin synthesis and handleability during preparation of a cured product. The melt viscosity (150°C) here is measured using an ICI viscometer in accordance with ASTM D4287.

[0035] <Epoxy resin> The present invention relates to an epoxy resin which is a reaction product of a catechol compound and an aliphatic ketone, the epoxy resin being characterized in that it is a reaction product having a phenolic resin having at least two catechol skeletons derived from the catechol compound, and a glycidyl ether group obtained by a reaction between a phenolic hydroxyl group of the phenolic resin and an epihalohydrin. The epoxy resin is an epoxy resin into which a glycidyl ether group has been introduced by reacting a phenolic hydroxyl group of the phenol resin with epihalohydrin, and a cured product using the epoxy resin is preferable because it has excellent heat resistance and high bending properties (such as bending strength and bending modulus).

[0036] As the epoxy resin, for example, an epoxy resin having a glycidyl ether group (the "OX group" in formula (4)) represented by the following general formula (4) can be obtained by reacting a phenolic hydroxyl group of a phenol resin represented by the above general formula (3) with epihalohydrin. [ka] [ka]

[0037] In the above general formula (4), X is represented by the above general formula (5), and R 4 is preferably a hydrogen atom or a methyl group, and more preferably a hydrogen atom. 4 However, when X is a hydrogen atom or the like, the bending property and heat resistance are excellent, which is preferable. Among them, when X is a hydrogen atom, the melt viscosity is low, which is a particularly preferable embodiment. Note that all of X may be substituted with the glycidyl group represented by the above formula (5), or a part of X may be substituted.

[0038] In the above general formula (4), R 1 , R 2 , R 3 , m, and n are the same as those in the above general formulae (1) to (3).

[0039] The phenolic resin can be reacted with epihalohydrin to obtain the desired epoxy resin. For example, the reaction may be carried out by using 2 to 10 moles of epihalohydrin per mole of phenolic hydroxyl groups in the phenolic resin, and reacting at a temperature of 20 to 120° C. for 0.5 to 30 hours while adding 0.9 to 2.0 moles of a basic catalyst per mole of phenolic hydroxyl groups all at once or in portions.

[0040] Specific examples of the basic catalyst include alkaline earth metal hydroxides, alkali metal carbonates, and alkali metal hydroxides. Among these, alkali metal hydroxides are preferred from the viewpoint of excellent catalytic activity, and specifically, sodium hydroxide, potassium hydroxide, and the like are preferred.

[0041] After the reaction is completed, the reaction mixture is washed with water, and then the unreacted epihalohydrin and the organic solvent are distilled off by heating under reduced pressure. In order to obtain an epoxy resin with even less hydrolyzable halogen, the obtained epoxy resin can be dissolved in an organic solvent again, and an aqueous solution of an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be added to further react. In this case, a phase transfer catalyst such as a quaternary ammonium salt or a crown ether can be present in order to improve the reaction rate. When a phase transfer catalyst is used, the amount used is preferably 0.1 to 3.0 parts by mass relative to 100 parts by mass of the epoxy resin. After the reaction is completed, the salt formed is removed by filtration or washing with water, and the organic solvent is distilled off under heating under reduced pressure to obtain the desired epoxy resin of the present invention.

[0042] The epoxy equivalent of the epoxy resin is preferably 120 to 400 g / equivalent, more preferably 130 to 300 g / equivalent, and even more preferably 120 to 200 g / equivalent. When the epoxy equivalent of the epoxy resin is within the above range, the crosslink density of the cured product is increased, and the heat resistance of the obtained cured product is excellent, which is preferable. The epoxy equivalent here is measured based on JIS K7236.

[0043] The melt viscosity (150°C) of the epoxy resin is preferably 2.0 dPa·s or less, more preferably 0.01 to 1.0 dPa·s, and even more preferably 0.1 to 0.6 dPa·s. When the melt viscosity of the epoxy resin is within the above range, the epoxy resin has low viscosity and excellent fluidity and handleability, and therefore the moldability of the obtained cured product is also excellent, which is preferable. The melt viscosity (150°C) here is measured using an ICI viscometer in accordance with ASTM D4287.

[0044] <Curable resin composition> The present invention relates to a curable resin composition containing the epoxy resin. The curable resin composition contains the epoxy resin, and thus the curable resin composition has excellent handleability and the obtained cured product has high heat resistance and high bending properties (such as bending strength and bending modulus), making it useful.

[0045] The curable resin composition of the present invention may further contain, in addition to the epoxy resin, other resins (including other epoxy resins), curing agents, additives, solvents, etc., within the scope of not impairing the effects of the present invention.

[0046] [Other epoxy resins] As the other epoxy resin, various epoxy resins can be used, and examples thereof include naphthalene skeleton-containing epoxy resins such as 2,7-diglycidyloxynaphthalene, α-naphthol novolac type epoxy resins, β-naphthol novolac type epoxy resins, polyglycidyl ether of α-naphthol / β-naphthol co-condensed type novolac, naphthol aralkyl type epoxy resins, and 1,1-bis(2,7-diglycidyloxy-1-naphthyl)alkane; bisphenol type epoxy resins such as bisphenol A type epoxy resins and bisphenol F type epoxy resins; biphenyl type epoxy resins such as biphenyl type epoxy resins and tetramethylbiphenyl type epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, and biphenyl novolac type epoxy resins; tetraphenylethane type epoxy resins; dicyclopentadiene-phenol addition reaction type epoxy resins; phenol aralkyl type epoxy resins; and phosphorus atom-containing epoxy resins. Examples of the phosphorus-containing epoxy resin include an epoxidized product of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (hereinafter abbreviated as "HCA"), an epoxidized product of a phenolic resin obtained by reacting HCA with quinones, an epoxy resin obtained by modifying a phenol novolac epoxy resin with HCA, an epoxy resin obtained by modifying a cresol novolac epoxy resin with HCA, an epoxy resin obtained by modifying a bisphenol A epoxy resin with a phenolic resin obtained by reacting HCA with quinones, etc. These may be used alone or in combination of two or more kinds.

[0047] [Other resins] The curable resin composition of the present invention may contain other resins in addition to the epoxy resin and other epoxy resins. In this specification, the term "other resins" refers to resins other than epoxy resins.

[0048] Specific examples of the other resins include, but are not limited to, active esters, maleimide resins, bismaleimide resins, polymaleimide resins, polyphenylene ether resins, polyimide resins, cyanate ester resins, benzoxazine resins, triazine-containing cresol novolac resins, cyanate ester resins, styrene-maleic anhydride resins, allyl group-containing resins such as diallyl bisphenol and triallyl isocyanurate, polyphosphate esters, phosphate ester-carbonate copolymers, etc. These other resins may be used alone or in combination of two or more.

[0049] [Hardening agent] The epoxy resin composition of the present invention may contain a curing agent together with the epoxy resin. By containing the curing agent, a cured product having excellent heat resistance can be obtained.

[0050] The curing agent used here includes an amine compound, an amide compound, an acid anhydride, a phenolic resin, etc., which may be used alone or in combination of two or more. The phenolic resin used as the curing agent is different from the phenolic resin having the specific structure in the present invention.

[0051] Examples of the amine compound include diaminodiphenylmethane, diethylenetriamine, triethylenetetramine, diaminodiphenylsulfone, isophoronediamine, imidazole, BF3-amine complex, and guanidine derivatives.

[0052] Examples of the amide-based compound include dicyandiamide, aliphatic dibasic acids, dimer acids, and polyamide resins synthesized from carboxylic acid compounds of fatty acids and amines such as ethylenediamine.

[0053] Examples of the acid anhydride include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.

[0054] Examples of the phenol resin include phenol novolac resin, cresol novolac resin, aromatic hydrocarbon formaldehyde resin modified phenol resin, dicyclopentadiene phenol addition type resin, phenol aralkyl resin (Zylok resin), polyhydric phenol novolac resin synthesized from a polyhydric hydroxy compound represented by resorcin novolac resin and formaldehyde, naphthol aralkyl resin, trimethylol methane resin, tetraphenylol ethane resin, naphthol novolac resin, naphthol-phenol co-condensed novolac resin, naphthol Examples of polyphenol compounds include cresol co-condensed novolac resins, biphenyl-modified phenolic resins (polyphenol compounds in which phenol nuclei are linked by bismethylene groups), biphenyl-modified naphthol resins (polyphenol compounds in which phenol nuclei are linked by bismethylene groups), aminotriazine-modified phenolic resins (polyphenol compounds in which phenol nuclei are linked by melamine, benzoguanamine, etc.), and alkoxy group-containing aromatic ring-modified novolac resins (polyphenol compounds in which phenol nuclei and alkoxy group-containing aromatic rings are linked by formaldehyde).

[0055] These curing agents may be used alone or in combination of two or more kinds.

[0056] In the curable resin composition of the present invention, the blending ratio of the epoxy resin component and the curing agent is preferably such that the amount of active groups in the curing agent is 0.7 to 1.5 equivalents per total equivalent of epoxy groups in the epoxy resin component, since this gives a cured product with excellent curability, heat resistance and toughness.

[0057] Examples of the additives include various additives such as a curing accelerator, a flame retardant, an inorganic filler, a silane coupling agent, a release agent, a pigment, an emulsifier, and a solvent, and these can be contained in the curable resin composition as necessary.

[0058] [Cure accelerator] Examples of the curing accelerator include phosphorus compounds, tertiary amines, imidazoles, organic acid metal salts, Lewis acids, amine complex salts, etc. Among them, from the viewpoint of excellent curing properties, heat resistance, electrical properties, moisture resistance reliability, etc., preferred are 2-ethyl-4-methylimidazole as an imidazole compound, triphenylphosphine as a phosphorus compound, and 1,8-diazabicyclo-[5.4.0]-undecene (DBU) as a tertiary amine.

[0059] [Flame retardant] Examples of the flame retardant include inorganic phosphorus compounds such as red phosphorus, ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate, and phosphoric acid amides; phosphoric acid ester compounds, phosphonic acid compounds, phosphinic acid compounds, phosphine oxide compounds, phosphorane compounds, organic nitrogen-containing phosphorus compounds, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide. and organic phosphorus compounds such as cyclic organic phosphorus compounds such as 10-(2,7-dihydroxynaphthyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide and derivatives thereof reacted with compounds such as epoxy resins and phenolic resins; nitrogen-based flame retardants such as triazine compounds, cyanuric acid compounds, isocyanuric acid compounds, and phenothiazine; silicone-based flame retardants such as silicone oils, silicone rubbers, and silicone resins; and inorganic flame retardants such as metal hydroxides, metal oxides, metal carbonate compounds, metal powders, boron compounds, and low-melting glass. When these flame retardants are used, the content of the flame retardants is preferably in the range of 0.1 to 20 mass % in the curable resin composition.

[0060] [Inorganic filler] The inorganic filler is blended, for example, when the curable resin composition of the present invention is used for semiconductor encapsulation material applications. Examples of the inorganic filler include fused silica, crystalline silica, alumina, silicon nitride, and aluminum hydroxide. Among them, the fused silica is preferred because it allows more inorganic filler to be blended. The fused silica can be used in either crushed or spherical form, but it is preferred to mainly use spherical silica in order to increase the blending amount of fused silica and suppress the increase in the melt viscosity of the curable resin composition. Furthermore, in order to increase the blending amount of spherical silica, it is preferred to appropriately adjust the particle size distribution of the spherical silica. The filling rate is preferably blended in the range of 0.5 to 95 parts by mass in 100 parts by mass of the curable resin composition.

[0061] The curable resin composition of the present invention may be prepared without a solvent or may contain a solvent. The solvent has a function of adjusting the viscosity of the curable resin composition. Specific examples of the solvent include, but are not limited to, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether-based solvents such as diethyl ether and tetrahydrofuran; ester-based solvents such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene, xylene, ethylbenzene, mesitylene, 1,2,3-trimethylbenzene, and 1,2,4-trimethylbenzene; and amide-based solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. These solvents may be used alone or in combination of two or more.

[0062] In addition, when the curable resin composition of the present invention is used for applications such as a conductive paste, a conductive filler such as silver powder or copper powder can be used.

[0063] <Cured product> The present invention relates to a cured product obtained by subjecting the curable resin composition to a curing reaction. Since the cured product is obtained from the curable resin composition containing the epoxy resin, it is preferable that the cured product exhibits high heat resistance and high bending properties (such as bending strength and bending modulus).

[0064] The curable resin composition of the present invention is obtained by uniformly mixing the above-mentioned components. The epoxy resin component, the curing agent, and if necessary, a curing accelerator are blended, and a cured product can be easily obtained by the same method as the conventionally known method. The obtained cured product includes molded cured products such as laminates, cast products, adhesive layers, coating films, and films.

[0065] As a method for obtaining a cured product by subjecting the curable resin composition to a curing reaction, for example, the heating temperature during heat curing is not particularly limited, but is preferably 100 to 300° C., and the heating time is preferably 1 to 24 hours.

[0066] <Uses of the curable resin composition> Examples of applications in which the curable resin composition is used include printed wiring board materials, resin compositions for flexible wiring boards, interlayer insulating materials for build-up boards, insulating materials for circuit boards such as adhesive films for build-up, resin casting materials, adhesives, semiconductor encapsulation materials, semiconductor devices, prepregs, conductive pastes, build-up films, build-up boards, fiber-reinforced composite materials, and molded products obtained by curing the composite materials. Among these various applications, in the applications of printed wiring board materials, insulating materials for circuit boards, and adhesive films for build-up, the composition can be used as an insulating material for so-called electronic component-embedded boards in which passive components such as capacitors and active components such as IC chips are embedded in the board. Furthermore, among the above, taking advantage of the characteristics of the cured product having excellent high heat resistance and high elastic modulus, the curable resin composition of the present invention is preferably used for semiconductor encapsulation materials, semiconductor devices, prepregs, flexible wiring boards, circuit boards, build-up films, build-up boards, multilayer printed wiring boards, fiber-reinforced composite materials, and molded products obtained by curing the composite materials. A method for producing the fiber-reinforced composite material from the curable resin composition will be described below.

[0067] 1. Semiconductor encapsulation materials As a method for obtaining a semiconductor encapsulation material from the curable resin composition, the curable resin composition, the curing accelerator, and compounding agents such as inorganic fillers are melt-mixed sufficiently until they are homogeneous using an extruder, kneader, roll, etc. as necessary. In this case, fused silica is usually used as the inorganic filler, but when used as a high thermal conductivity semiconductor encapsulation material for power transistors and power ICs, it is preferable to use highly filled crystalline silica, alumina, silicon nitride, etc., which have a higher thermal conductivity than fused silica, or fused silica, crystalline silica, alumina, silicon nitride, etc. The filling rate is preferably in the range of 30 to 95 parts by mass per 100 parts by mass of the curable resin composition, and among them, in order to improve flame retardancy, moisture resistance, and solder crack resistance and to reduce the linear expansion coefficient, it is more preferable that the inorganic filler is 70 parts by mass or more, and even more preferable that the inorganic filler is 80 parts by mass or more.

[0068] 2. Semiconductor Devices As a method for obtaining a semiconductor device from the above-mentioned curable resin composition, the above-mentioned semiconductor encapsulating material is molded by casting or using a transfer molding machine, an injection molding machine or the like, and then heated at 50 to 200°C for 2 to 10 hours.

[0069] 3. Prepreg As a method for obtaining a prepreg from the curable resin composition, a method can be mentioned in which the curable resin composition is made into a varnish by blending the following organic solvent, and then impregnated into a reinforcing substrate (paper, glass cloth, glass nonwoven fabric, aramid paper, aramid cloth, glass mat, glass roving cloth, etc.), and then heated at a heating temperature according to the type of solvent used, preferably at 50 to 170° C. The mass ratio of the resin composition to the reinforcing substrate used at this time is not particularly limited, but it is usually preferable to prepare the resin content in the prepreg to be 20 to 60 mass%.

[0070] Examples of the organic solvent used herein include methyl ethyl ketone, acetone, dimethylformamide, methyl isobutyl ketone, methoxypropanol, cyclohexanone, methyl cellosolve, ethyl diglycol acetate, and propylene glycol monomethyl ether acetate. The selection and appropriate amount of the organic solvent used can be appropriately selected depending on the application. For example, when a printed circuit board is further produced from the prepreg as described below, it is preferable to use a polar solvent having a boiling point of 160° C. or less, such as methyl ethyl ketone, acetone, or dimethylformamide, and it is also preferable to use such a polar solvent in such a proportion that the nonvolatile content is 40 to 80 mass%.

[0071] 4. Circuit Board A method for obtaining a printed circuit board from the curable resin composition includes laminating the prepreg by a conventional method, appropriately overlaying copper foil, and subjecting the laminate to heat-pressure bonding at 170 to 300° C. under a pressure of 1 to 10 MPa for 10 minutes to 3 hours.

[0072] 5. Flexible wiring board The method for producing a flexible wiring board from the curable resin composition includes a method consisting of the following three steps: The first step is a step of applying a curable resin composition containing an active ester, an epoxy resin, and an organic solvent to an electrical insulating film using a coater such as a reverse roll coater or a comma coater, the second step is a step of heating the electrical insulating film to which the curable resin composition has been applied at 60 to 170°C for 1 to 15 minutes using a heater to volatilize the solvent from the electrical insulating film and to bring the curable resin composition to a B-stage, and the third step is a step of thermocompressing a metal foil to an adhesive using a heating roll or the like (the compression pressure is preferably 2 to 200 N / cm and the compression temperature is preferably 40 to 200°C) on the electrical insulating film to which the curable resin composition has been brought to a B-stage. If sufficient adhesive performance is obtained by going through the above three steps, the process may be terminated here, but if complete adhesive performance is required, it is preferable to further post-cure under conditions of 100 to 200° C. for 1 to 24 hours. The thickness of the curable resin composition film after final curing is preferably in the range of 5 to 100 μm.

[0073] 6. Build-up board The method for producing a build-up board from the curable resin composition includes a method consisting of the following three steps. The first step is a step of applying the curable resin composition, which is appropriately blended with rubber, filler, etc., to a circuit board on which a circuit is formed, using a spray coating method, a curtain coating method, etc., and then curing the composition. The second step is a step of forming a predetermined through-hole portion or the like as necessary, treating the surface with a roughening agent, washing the surface with hot water to form unevenness, and plating a metal such as copper. The third step is a step of repeating such operations in sequence as desired to alternately build up and form a resin insulating layer and a conductor layer of a predetermined circuit pattern. It is preferable to form a through-hole portion after forming the outermost resin insulating layer. The first step can be performed by laminating a build-up film that has been coated and dried to a desired thickness in advance, in addition to the above-mentioned solution coating. In addition, the build-up board of the present invention can be produced by forming a roughened surface by semi-curing the resin composition on the copper foil, and then heat-pressing the resulting resin-coated copper foil onto a wiring board having a circuit formed thereon at 170 to 250°C, thereby eliminating the need for a plating process.

[0074] 7. Build-up film A method for producing a build-up film from the curable resin composition includes applying the curable resin composition onto a support film to form a curable resin composition layer to form an adhesive film for a multilayer printed wiring board.

[0075] When producing a build-up film from a curable resin composition, it is essential that the film softens under the temperature conditions for lamination in a vacuum lamination method (usually 70 to 140°C) and exhibits fluidity (resin flow) that allows the resin to fill via holes or through holes present in the circuit board at the same time as lamination of the circuit board, and it is preferable to blend the above-mentioned components so as to exhibit such properties.

[0076] Here, the diameter of the through-holes in the multilayer printed wiring board is usually 0.1 to 0.5 mm, and the depth is usually 0.1 to 1.2 mm, and it is usually preferable to enable resin filling within this range. When both sides of the circuit board are laminated, it is preferable to fill about 1 / 2 of the through-holes.

[0077] Specifically, the adhesive film can be produced by preparing the curable resin composition in a varnish form, applying the varnish-like composition to the surface of the support film (Y), and then drying the organic solvent by heating or blowing hot air or the like to form a composition layer (X) made of the curable resin composition.

[0078] The thickness of the composition layer (X) formed is usually preferably equal to or greater than the thickness of the conductor layer. Since the thickness of the conductor layer of the circuit board is usually in the range of 5 to 70 μm, the thickness of the resin composition layer is preferably 10 to 100 μm.

[0079] The composition layer (X) in the present invention may be protected with a protective film described below. By protecting the resin composition layer with a protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be prevented.

[0080] Examples of the support film and protective film include polyolefins such as polyethylene, polypropylene, and polyvinyl chloride, polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate, polycarbonate, polyimide, and further release paper and metal foils such as copper foil and aluminum foil. The support film and protective film may be subjected to a release treatment in addition to a mud treatment and a corona treatment.

[0081] The thickness of the support film is not particularly limited, but is usually in the range of 10 to 150 μm, preferably 25 to 50 μm, and the thickness of the protective film is preferably 1 to 40 μm.

[0082] The above-mentioned support film (Y) is peeled off after laminating it onto the circuit board or after forming an insulating layer by heat curing. If the support film (Y) is peeled off after the adhesive film is heat cured, the adhesion of dust and the like during the curing process can be prevented. When peeling off after curing, the support film is usually subjected to a release treatment in advance.

[0083] 8. Multilayer printed wiring boards The film obtained as described above can also be used to manufacture a multilayer printed wiring board. In the method for manufacturing such a multilayer printed wiring board, for example, when the composition layer (X) is protected by a protective film, the protective film is peeled off, and then the composition layer (X) is directly laminated on one or both sides of the circuit board by, for example, a vacuum lamination method. The lamination method may be a batch method or a continuous method using a roll. In addition, the adhesive film and the circuit board may be heated (preheated) before lamination as necessary.

[0084] The lamination conditions are a pressure-bonding temperature (lamination temperature) of preferably 70 to 140°C and a pressure-bonding pressure of preferably 1 to 11 kgf / cm. 2 (9.8×10 4 ~107.9×10 4 N / m 2 ) and lamination is preferably performed under reduced pressure of 20 mmHg (26.7 hPa) or less.

[0085] 9. Fiber-reinforced composite materials The present invention relates to a fiber-reinforced composite material comprising the curable resin composition and reinforcing fibers. The fiber-reinforced composite material can be produced from the curable resin composition by uniformly mixing each component constituting the curable resin composition to prepare a varnish, impregnating the varnish into a reinforcing base material made of reinforcing fibers, and then polymerizing the varnish. In particular, the epoxy resin of the present invention has a low melt viscosity and is therefore excellent in handleability, making it suitable for producing the fiber-reinforced composite material and preferable.

[0086] Specifically, the curing temperature when carrying out such a polymerization reaction is preferably in the range of 50 to 250°C. In particular, it is preferable to carry out curing at 50 to 100°C to form a tack-free cured product, and then further treat it at a temperature of 120 to 200°C.

[0087] Here, the reinforcing fibers may be any of twisted yarns, untwisted yarns, and non-twisted yarns, but untwisted yarns and non-twisted yarns are preferred because they provide both moldability and mechanical strength for the fiber-reinforced plastic member. Furthermore, the form of the reinforcing fibers may be one in which the fibers are aligned in one direction or a woven fabric. For the woven fabric, a plain weave, a satin weave, or the like may be freely selected according to the part to be used and the application. Specifically, carbon fibers, glass fibers, aramid fibers, boron fibers, alumina fibers, silicon carbide fibers, and the like, which are excellent in mechanical strength and durability, may be used, and two or more of these may be used in combination. Among these, carbon fibers are preferred because they provide good strength for the molded product, and various types of carbon fibers such as polyacrylonitrile, pitch, and rayon may be used. Among these, polyacrylonitrile-based fibers are preferred because they can easily provide high-strength carbon fibers. Here, when the varnish is impregnated into a reinforcing base material made of reinforcing fibers to produce a fiber-reinforced composite material, the amount of reinforcing fibers used is preferably an amount such that the volume content of the reinforcing fibers in the fiber-reinforced composite material is in the range of 40 to 85%.

[0088] 10. Fiber-reinforced plastic moldings The present invention relates to a fiber-reinforced resin molded article containing the cured product and reinforcing fibers. Examples of methods for producing a fiber-reinforced resin molded article from the curable resin composition include a hand lay-up method or a spray-up method in which fiber aggregates are laid in a mold and the varnish is multi-layered; a vacuum bag method in which a base material made of reinforcing fibers is impregnated with the varnish and stacked using either a male or female mold, and a flexible mold capable of applying pressure to the molded article is placed over the molded article, which is hermetically sealed and vacuum (reduced pressure) molded; an SMC press method in which a sheet of varnish containing reinforcing fibers is compressed and molded in a mold; and an RTM method in which the varnish is injected into a mating mold in which fibers are laid out, to produce a prepreg in which the reinforcing fibers are impregnated with the varnish, which is then baked and hardened in a large autoclave. In particular, the epoxy resin of the present invention has a low melt viscosity and is therefore excellent in handleability, making it suitable for producing the fiber-reinforced resin molded article, and is therefore preferable. The fiber-reinforced resin molded product obtained above is a molded product having reinforcing fibers and a cured product of the curable resin composition. Specifically, the amount of reinforcing fibers in the fiber-reinforced resin molded product is preferably in the range of 40 to 70 mass %, and from the viewpoint of strength, it is particularly preferably in the range of 50 to 70 mass %.

[0089] 11.Other Although the method for producing a semiconductor encapsulation material, a fiber-reinforced composite material, etc. has been described above, other cured products can also be produced from the curable resin composition. The other cured products can be produced according to a general curing method for a curable resin composition. For example, the heating temperature conditions may be appropriately selected depending on the type of curing agent to be combined, the application, etc. EXAMPLES

[0090] The present invention will be described in detail below with reference to examples and comparative examples, but should not be construed as being limited thereto. In the following, unless otherwise specified, all values ​​are by mass. The phenolic resins and epoxy resins obtained below, and the cured products obtained using the epoxy resins, were measured and evaluated under the following conditions.

[0091] <Hydroxyl equivalent of phenolic resin> The hydroxyl equivalent weight (g / equivalent) of the phenolic resin was measured according to the procedure and calculation formula shown below. 2.5g of the phenolic resin obtained below was weighed out, along with 7.5g of triphenylphosphine, 7.5g of pyridine, and 2.5g of acetic anhydride, in a 500mL Erlenmeyer flask and treated at 120℃ for 2.5 hours, after which 5mL of distilled water was added to stop the reaction.Then, the sample was dissolved in 150mL of tetrahydrofuran and 200mL of propylene glycol monomethyl ether to prepare a sample solution. Separately from the sample solution, 10 mL of distilled water and 2.5 g of acetic anhydride were precisely weighed, 10 g of pyridine was added, and the mixture was stirred for 10 minutes and allowed to stand for 20 minutes. Then, 150 mL of tetrahydrofuran and 200 mL of propylene glycol monomethyl ether were mixed to prepare a blank solution. The obtained sample solution and blank solution were titrated with a 0.5 mol / L ethanolic potassium hydroxide solution (titration solution) using an automatic potentiometric titrator AT-510 (Kyoto Electronics Manufacturing Co., Ltd.), and the hydroxyl equivalent was calculated using the following formula.

[0092] [Blank formula] BL = (titer of blank solution) x (theoretical titer of 2.5 g of acetic anhydride) / (theoretical titer of blank solution) =Y×[(2.5 / 102.09)×2×(1000 / 5)] / [(W / 102.09)×2×(1000 / 5)] BL: blank value (mL) Y: Titration volume of blank solution (mL) W: Amount of acetic anhydride in blank measurement (g)

[0093] [Formula for calculating the hydroxyl equivalent of a sample] Hydroxyl equivalent (g / eq) = S x 1000 / [{(BL x FA3 / FA5)-EP1} x FA4] S: Sample size (g) FA3: Amount of acetic anhydride at the time of sample measurement (g) FA4: Concentration of the titrant (ethanol KOH solution) (mol / L) FA5: Amount of acetic anhydride during sample measurement (g) EP1: Titration volume of the sample (mL)

[0094] <Measurement of melt viscosity (at 150 °C)> In accordance with ASTM D4287, the melt viscosity (dPa·s) at 150 °C was measured using an ICI viscometer.

[0095] <Measurement of viscosity (at 25 °C)> Using an E-type viscometer (TV-22 manufactured by Toki Sangyo Co., Ltd.), the viscosity (mPa·s) at 25 °C was measured.

[0096] <Epoxy equivalent of epoxy resin> In accordance with JIS K7236, the epoxy equivalent (g / equivalent) of the epoxy resin obtained below was measured.

[0097] <Measurement of GPC> Using the following measuring apparatus and measuring conditions, the synthesis confirmation of the phenolic resin obtained by the following synthesis method and the calculation of the content ratio (area%) of the remaining (unreacted) catechol compound in the phenolic resin were performed based on GPC measurement. Also, regarding the synthesis confirmation of the target product (epoxy resin), it was confirmed by the disappearance of the peak derived from the phenolic resin based on GPC measurement. Measuring apparatus: "HLC-8320 GPC" manufactured by Tosoh Corporation Column: Guard column "HXL-L" manufactured by Tosoh Corporation + "TSK-GEL G2000HXL" manufactured by Tosoh Corporation + "TSK-GEL G2000HXL" manufactured by Tosoh Corporation + "TSK-GEL G3000HXL" manufactured by Tosoh Corporation + "TSK-GEL G4000HXL" manufactured by Tosoh Corporation Detector: RI (differential refractometer) Data processing: "GPC Workstation EcoSEC-WorkStation" manufactured by Tosoh Corporation Measurement conditions: Column temperature 40℃ Developing solvent: Tetrahydrofuran Flow rate 1.0ml / min Standard: In accordance with the measurement manual for the aforementioned "GPC Workstation EcoSEC-WorkStation," the following monodisperse polystyrene with known molecular weight was used. (Polystyrene used) "A-500" manufactured by Tosoh Corporation "A-1000" manufactured by Tosoh Corporation "A-2500" manufactured by Tosoh Corporation "A-5000" manufactured by Tosoh Corporation "F-1" manufactured by Tosoh Corporation "F-2" manufactured by Tosoh Corporation "F-4" manufactured by Tosoh Corporation "F-10" manufactured by Tosoh Corporation "F-20" manufactured by Tosoh Corporation "F-40" manufactured by Tosoh Corporation "F-80" manufactured by Tosoh Corporation "F-128" manufactured by Tosoh Corporation Sample: 1.0 mass% epoxy resin solid content calculated as tetrahydrofuran solution filtered through a microfilter (50 μl). Regarding the content (area %) of the residual (unreacted) catechol compound in the phenolic resin, from the viewpoint of reducing the volatile content during curing and avoiding adverse effects on the bending properties of the obtained cured product, the content of the residual catechol compound is preferably 20 area % or less.

[0098] [Synthesis Example 1] Synthesis of phenolic resin (P-1) A 2L flask equipped with a thermometer, a condenser, and a stirrer was charged with 495.5g (4.50mol) of catechol, 4.9g (0.046mol) of 3-mercaptopropionic acid, 247.8g of 1,4-dioxane, and 52.5g (0.54mol) of 98% sulfuric acid, and the temperature was raised to 40°C under nitrogen flow. While maintaining the temperature, 87.0g (1.55mol) of acetone was dropped over 1 hour, and the reaction was continued for another 3 hours. After the reaction, 520.0g of methyl isobutyl ketone was charged and washed with water until it became neutral. Next, the system was dehydrated by azeotropy, and after passing through microfiltration, it was concentrated under reduced pressure at 150°C. Furthermore, by distilling off unreacted catechol while blowing in water vapor, 236g of phenolic resin (P-1) was obtained (residual catechol was 3.9% by GPC area%). The phenol resin (P-1) had a hydroxyl equivalent of 72 g / equivalent and a melt viscosity (150°C) of 0.7 dPa·s, and its synthesis was confirmed by GPC measurement, the measurement results of which are shown in Figure 1.

[0099] [Synthesis Example 2] Synthesis of phenolic resin (P-2) A 2L flask equipped with a thermometer, a condenser, and a stirrer was charged with 200.0g (1.82mol) of catechol, 220.0g of 1,4-dioxane, and 35.0g (0.36mol) of 98% sulfuric acid, and the temperature was raised to 40°C under nitrogen flow. While maintaining the temperature, 60.0g (1.07mol) of acetone was dropped over 1 hour, and the reaction was continued for another 3 hours. After the reaction, 300.0g of methyl isobutyl ketone was charged and washed with water until it became neutral. Next, the system was dehydrated by azeotropy, and after passing through microfiltration, it was concentrated under reduced pressure at 150°C to obtain 160g of phenolic resin (P-2) (residual catechol was 13.4% in GPC area%). The hydroxyl equivalent of the phenol resin (P-2) was 71 g / equivalent, and the melt viscosity (150°C) was 0.6 dPa·s. The synthesis was confirmed by GPC measurement, the measurement results of which are shown in FIG. 2.

[0100] [Example 1] Synthesis of epoxy resin (E-1) A 2L flask equipped with a thermometer, a cooling tube, and a stirrer was charged with 170.0 g of phenolic resin (P-1) (2.36 mol as hydroxyl groups) and 873.6 g (9.44 mol) of epichlorohydrin, and the temperature was raised to 50 ° C. while stirring and dissolving. Next, 10.35 g of 50% tetramethylammonium aqueous solution was charged and reacted for 24 hours. Furthermore, 211.6 g of 49% sodium hydroxide aqueous solution (1.10 equivalents to hydroxyl groups) was dropped over 3 hours, and the reaction was further carried out at 50 ° C. for 1 hour. After the reaction was completed, 262.1 g of isopropyl alcohol was added, stirring was stopped, the water layer accumulated in the lower layer was removed, stirring was resumed, and unreacted epichlorohydrin was distilled off under reduced pressure at 150 ° C. 517.8 g of methyl isobutyl ketone was added to the obtained crude epoxy resin and dissolved, and washing with 152.3 g of water was repeated until the pH of the washing liquid became neutral. Next, the system was dehydrated by azeotropy, and after microfiltration, the solvent was distilled off under reduced pressure to obtain 270.0 g of the target epoxy resin (E-1). The obtained epoxy resin (E-1) was a viscous semi-solid at room temperature, with an epoxy equivalent of 152 g / equivalent and a melt viscosity (150°C) of 0.2 dPa·s, and its synthesis was confirmed by GPC measurement. The measurement results are shown in Figure 3.

[0101] [Example 2] Synthesis of epoxy resin (E-2) A 2L flask equipped with a thermometer, a cooling tube, and a stirrer was charged with 100.0 g of phenolic resin (P-2) (1.41 mol as hydroxyl groups) and 513.9 g (5.56 mol) of epichlorohydrin, and the temperature was raised to 50 ° C. while stirring and dissolving. Next, 6.09 g of 50% tetramethylammonium aqueous solution was charged and reacted for 24 hours. Furthermore, 124.7 g of 49% sodium hydroxide aqueous solution (1.10 equivalents relative to hydroxyl groups) was dropped over 3 hours, and the reaction was further carried out at 50 ° C. for 1 hour. After the reaction was completed, 154.2 g of isopropyl alcohol was added, stirring was stopped, the water layer accumulated in the lower layer was removed, stirring was resumed, and unreacted epichlorohydrin was distilled off under reduced pressure at 150 ° C. 614.1 g of methyl isobutyl ketone was added to the obtained crude epoxy resin and dissolved, and washing with 180.6 g of water was repeated until the pH of the washing liquid became neutral. Next, the system was dehydrated by azeotropy, and after microfiltration, the solvent was distilled off under reduced pressure to obtain 160.0 g of the target epoxy resin (E-2). The epoxy equivalent of the obtained epoxy resin (E-2) was 158 g / equivalent, and the melt viscosity (150°C) was 0.1 dPa·s, and its synthesis was confirmed by GPC measurement. The measurement results are shown in Figure 4.

[0102] [Comparative Example 1] Synthesis of epoxy resin (E-3) In a 2L flask equipped with a thermometer, a condenser, and a stirrer, 165.0g (1.5mol) of catechol and 1110g (12mol) of epichlorohydrin were charged, and the temperature was raised to 50°C while stirring and dissolving. Next, 11.2g of benzyltrimethylammonium chloride was charged, and the mixture was reacted for 15 hours at a temperature of 50°C. Furthermore, 269.4g of 49% aqueous sodium hydroxide solution (1.10mol relative to hydroxyl groups) was dropped over 3 hours, and the mixture was reacted for another hour at 50°C. After the reaction was completed, 222.0g of n-butanol was added, stirring was stopped, the water layer that had accumulated in the lower layer was removed, stirring was resumed, and unreacted epichlorohydrin was distilled off under reduced pressure at 150°C. 566.1g of methyl isobutyl ketone and 94.5g of n-butanol were added to the crude epoxy resin obtained and dissolved. Furthermore, 14.2 g of a 10% aqueous solution of sodium hydroxide was added to this solution and reacted at 80°C for 2 hours, after which washing with 185.0 g of water was repeated until the pH of the washings became neutral. Next, the system was dehydrated by azeotropy, and after microfiltration, the solvent was distilled off under reduced pressure to obtain 323.0 g of epoxy resin (E-3). The epoxy equivalent of the obtained epoxy resin (E-3) was 137 g / equivalent, and the viscosity (25°C) was 1900 mPa·s, and its synthesis was confirmed by GPC measurement. The measurement results are shown in Figure 5.

[0103] [Comparative Example 2] Epoxy resin (E-4) Bisphenol A type epoxy resin EPICLON 850S (epoxy equivalent: 188 g / equivalent) manufactured by DIC Corporation was used as epoxy resin (E-4). The viscosity (25°C) was 13,500 mPa·s.

[0104] [Examples 3-4, Comparative Examples 3-4] The obtained epoxy resin and 4,4'-diaminodiphenylsulfone as a curing agent were mixed so that the ratio of [epoxy equivalent / active hydrogen equivalent] was 1 / 1, and melt mixed at 120°C to obtain an epoxy resin composition. The epoxy resin composition was then poured between glass plates sandwiching 2 mm and 4 mm spacers, and cured at 150°C for 1 hour and then at 180°C for 3 hours to produce a cured product.

[0105] <Glass transition temperature (Tg)> The obtained cured product with a thickness of 2 mm was cut into a size of 5 mm in width and 20 mm in length to prepare a test piece. The test piece was measured using a viscoelasticity measuring device (DMA: Hitachi High-Tech Science Corporation solid viscoelasticity measuring device "DMS6100", deformation mode: double-support bending, measurement mode: sine wave vibration, frequency 1 Hz, heating rate 3°C / min) to evaluate the temperature at which the elastic modulus change was maximum (the rate of change in tan δ was the largest) as the glass transition temperature. The glass transition temperature (Tg) is preferably not less than 220° C., and more preferably not less than 230° C. If it is within the above range, high heat resistance can be exhibited, and the composition is useful.

[0106] <Measurement of bending strength, bending modulus, bending strain> The obtained cured product was cut into a size of 2 mm in thickness, 10 mm in width, and 80 mm in length, which was used as test piece 2. The bending strength, bending modulus, and bending strain of test piece 2 were measured according to JIS K6911 using a precision universal testing machine ("AUTOGRAPH AG-I" manufactured by Shimadzu Corporation). The flexural modulus is preferably 3000 MPa or more, and more preferably 3500 MPa or more. The bending strength is preferably 120 MPa or more, and more preferably 130 MPa or more. The bending strain is preferably 3% or more, and more preferably 4% or more. If it is within the above range, high bending properties can be exhibited, which is useful.

[0107] [Table 1]

[0108] From the evaluation results in Table 1 above, it was confirmed that in Examples 3 and 4, by using epoxy resins obtained by using the phenolic resins having the desired specific structures obtained in Examples 1 and 2, it was possible to obtain cured products with high bending properties and high heat resistance. On the other hand, in Comparative Example 3, the desired phenolic resin obtained by reacting a catechol compound with an aliphatic ketone as in the Examples was not used, but the catechol-type epoxy resin obtained in Comparative Example 1, which was synthesized using only the catechol compound, was used, so that the glass transition temperature was very low and it was not possible to achieve both heat resistance and bending properties. In addition, in Comparative Example 4, a commonly used bisphenol A type epoxy resin (Comparative Example 2) was used, but the glass transition temperature and flexural modulus were lower than those of the Examples, and it was not possible to achieve both heat resistance and flexural properties. [Brief description of the drawings]

[0109] [Figure 1] 1 is a GPC spectrum chart of the phenol resin (P-1) obtained in Synthesis Example 1. [Diagram 2] 1 is a GPC chart of the phenol resin (P-2) obtained in Synthesis Example 2. [Diagram 3] 1 is a GPC chart of the epoxy resin (E-1) obtained in Example 1. [Figure 4] 1 is a GPC chart of the epoxy resin (E-2) obtained in Example 2. [Diagram 5] 1 is a GPC chart of the epoxy resin (E-3) obtained in Comparative Example 1.

Claims

1. A phenolic resin which is a reaction product of a catechol compound and an aliphatic ketone and has at least two catechol skeletons derived from the catechol compound; The epoxy resin is a reaction product having a glycidyl ether group obtained by reacting a phenolic hydroxyl group of the phenol resin with an epihalohydrin, and is represented by the following general formula (4): 【Chemistry 4】 【Chemistry 5】 (In the above general formula (4), R 1 is a hydrogen atom, R 2 and R 3 are each independently a hydrocarbon group having 1 to 4 carbon atoms, m is an integer of 0 to 3, n is an integer of 0 to 3, and X is represented by the above general formula (5), and R 4 is a hydrogen atom or a methyl group.

2. A curable resin composition comprising the epoxy resin according to claim 1.

3. A cured product obtained by subjecting the curable resin composition according to claim 2 to a curing reaction.

4. A fiber-reinforced composite material comprising the curable resin composition according to claim 2 and reinforcing fibers.

5. A fiber-reinforced resin molded product comprising the cured product according to claim 3 and reinforcing fibers.